American Journal of Criminal Justice The Journal of the Southern Criminal Justice Association - Miller, J. Mitchell; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The American Journal of Criminal Justice, the official journal of the Southern Criminal Justice Association, is a peer reviewed publication; manuscripts go through a blind review process. The focus of the Journal is on a wide array of criminal justice topics and issues. Some of these concerns include items pertaining to the criminal justice process, the formal and informal interplay between system components, problems and solutions experienced by various segments, innovative practices, policy development and implementation, evaluative research, the players engaged in these enterprises, and a wide assortment of other related interests. The American Journal of Criminal Justice publishes original articles that utilize a broad range of methodologies and perspectives when examining crime, law, and criminal justice processing.
Keywords: Criminology and Criminal Justice; Criminology and Criminal Justice, general